Determinants of poor access to health care among women of reproductive age in Sierra Leone: a cross-sectional study - Augustus Osborne; Peter Bai James; Camilla Bangura (BMC Health Services Research)
Abstract Background Sierra Leone, like many developing countries, faces challenges in ensuring equitable access to healthcare, particularly for women of reproductive age. This women has specific healthcare needs related to sexual and reproductive health, maternal health, and family planning. Despite improvements in national healthcare coverage, disparities persist, with women of reproductive age, especially those in rural areas and lower socio-economic brackets, experiencing significant barriers to accessing essential services. The study examined the factors associated with poor access to healthcare among women in Sierra Leone. Methods The study utilised the cross-sectional 2019 Sierra Leone Demographic Health Survey. The study included 15,574 women of reproductive age (15–49 years) in Sierra Leone. A mixed-effect multilevel binary logistic regression analysis was conducted, determining the factors associated with poor access to healthcare using a four-modeled approach. The results were presented as adjusted odds ratios (aOR) with a 95% confidence interval (CI). Results From our study the proportion of poor access to healthcare was 71.9% [69.7,74.0] in Sierra Leone. Previously married women(divorced, separated, or widowed) [aOR = 1.74; 95% CI: 1.30, 2.34] had higher odds of poor access to healthcare than those never in a union. Women living in rural areas [aOR = 1.88; 95% CI: 1.30, 2.71] had higher odds of poor access to healthcare than those living in urban areas. Women with secondary [aOR = 0.74; 95% CI: 0.62, 0.89] and higher education [aOR = 0.48; 95% CI: 0.34, 0.68] had lower odds of poor healthcare access than those without education. Women who watch television [aOR = 0.70; 95% CI: 0.56, 0.86] had lower odds of poor access to healthcare than those who did not. Richer [aOR = 0.57; 95% CI: 0.42, 0.79] and Richest quintile women [aOR = 0.45; 95% CI: 0.32, 0.65] have lower odds of poor access to healthcare than women in the poorest quintile. Women living in the Western region [aOR = 0.38; 95% CI: 0.22, 0.65] have lower odds of poor access to healthcare than those living in the Eastern region. Conclusion Our study revealed that poor access to healthcare is a significant issue in Sierra Leone. Women who were previously married (divorced, separated, or widowed), lived in rural areas, or had lower education levels faced higher odds of poor healthcare access. Conversely, women with higher education, greater wealth, watch television, and those residing in the Western region had significantly lower odds of poor healthcare access. These findings underscore the need for targeted interventions addressing socioeconomic, educational, and provincial disparities to improve healthcare access for women in Sierra Leone.